Down the up staircase : three generations of a Harlem family - Haynes, Bruce D., 1960-; Solovitch, Syma (Columbia University Press, 2017)
"Down the Up Staircase tells the history of three generations of a black middle-class family against the backdrop of the three-story brownstone at 411 Convent Avenue in the Sugar Hill section of Harlem. The home once belonged to its patriarch, George Edmund Haynes, a migrant from Pine Bluff, Arkansas, who went on to become the first African American to earn a PhD at Columbia University and found the National Urban League. He was the first prominent black economist in the country, the first to predict the great sweeping migration of blacks from the rural South to the urban North, a power broker of the Harlem Renaissance, and the first black to serve in a federal sub-cabinet post, where he mobilized the new Black migrants for the war effort. His wife, Elizabeth Ross Haynes, was a noted children's author of the period and a prominent social scientist. Yet these early advances and gains provided little anchor to the succeeding generations. Their son had dreamed of becoming an engineer but spent his entire career as a parole officer in the Bronx. Their eldest grandson graduated from the prestigious Horace Mann High School but spent much of his adult life in and out of drug rehabilitation clinics, psychiatric hospitals, and the streets. Their second grandson was slain on the streets of the Bronx during his last semester of college, at age twenty-three. Only the youngest grandson--the book's author, Bruce Haynes--was able to build on the gains of his forefathers. Haynes brings sociological insight to a familiar American tale, one where the notion of social mobility and black middle class is a tenuous term"--Provided by publisher.